Technical aspects in sarcoma surgery: a surgical survey among surgeons at sarcoma centers in Germany and Switzerland - Zygmunt, Anne-Christine; Yilmaz, Elif; Hettler, Madelaine; Ghadimi, Michael; Bösch, Florian; Jakob, Jens (Langenbeck's archives of surgery, 2025)
Surgery is a substantial pillar of extremity sarcoma treatment. There are no standardized, evidence-based strategies to perform a wide R0 resection which is recommended by international and German guidelines. The aim of this study was to use a standardized questionnaire combined with a semi-structured interview to survey the reality of surgical care in German and Swiss sarcoma centers and establish a rationale for future prospective studies to improve postoperative outcome and oncological quality in extremity sarcoma surgery.
Gesehen am 29.10.2025